Optimization of power control parameters for DS-CDMA cellular systems. - Abrardo, A.
This paper envisages a cellular system based on code-division multiple access and investigates the performance of a strength-based closed-loop power control (CLPC) scheme on the basis of different parameters, such as the number of bits of the power command, the quantization step size, and the user speed. On the basis of a log-linear CLPC model, an analytical approach has been developed that has allowed to determine the optimum quantization step size to be used for each value of the number of power command bits. Simulation results have permitted to support the analytical framework developed in this paper
Keywords: DS-CDMA cellular systems; Code-division multiple access; Log-linear CLPC model; Optimization; Optimum quantization step size; Power command; Power control parameters; Quantization step size; Strength-based closed-loop power control; User speed